2013
DOI: 10.1093/aob/mct102
|View full text |Cite
|
Sign up to set email alerts
|

Time-lapse imaging of self- and cross-pollinations in Brassica rapa

Abstract: Regulated hydration of pollen is a key process for both pollination and self-incompatibility, and this is achieved by a balanced complex of hydration, dehydration and nutrient supply to pollen grains from stigmatic papilla cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…Thus, inhibition of the incompatible pollen acts very early, within the first minutes following stigma contact, blocking pollen hydration. As previously described, hydration appears as the first check point controlling pollen rejection in SI species with dry stigma (Zuberi and Dickinson, 1985; Dickinson, 1995; Samuel et al , 2009; Hiroi et al , 2013; Safavian and Goring, 2013; Wang et al , 2016). In this study, the hydration threshold required to trigger germination was found to correspond to a pollen L/W ratio below 1.4.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Thus, inhibition of the incompatible pollen acts very early, within the first minutes following stigma contact, blocking pollen hydration. As previously described, hydration appears as the first check point controlling pollen rejection in SI species with dry stigma (Zuberi and Dickinson, 1985; Dickinson, 1995; Samuel et al , 2009; Hiroi et al , 2013; Safavian and Goring, 2013; Wang et al , 2016). In this study, the hydration threshold required to trigger germination was found to correspond to a pollen L/W ratio below 1.4.…”
Section: Discussionmentioning
confidence: 64%
“…Because the increase of water content in pollen grain is correlated with change of its shape from ellipsoid to spheroid (Zuberi and Dickinson, 1985; Hiroi et al , 2013; Wang et al , 2016), for each pollen grain, we recorded every two minutes the ratio between the long and the wide axis (L/W) to estimate the pollen hydration rate until germination. Slopes were determined by linear regression of the hydration curve based on pollen ratio evolution during the first 10 minutes period (5 data points), using the curve f = ax + b.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this system compatibility is established at the stigma surface within minutes of pollination when compatible grains gain access to stigmatic water, but incompatible pollen generally fail to fully hydrate and germinate. Thus, pollen hydration on the stigma surface is essential for successful reproduction and is a strictly regulated checkpoint centred in the stigma (Dickinson, 1995;Ma et al, 2012;Hiroi et al, 2013). Possession of a dry stigma comes with the requirement that the exine surface of conspecific pollen must carry a coating (tryphine) (Dickinson, 1995;Dickinson et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Papilla cells have various roles in this step, such as discrimination of pollen grains for inter- and intraspecies barriers, pollen hydration, supply of stigmatic resources for pollen germination and pollen tube elongation, and pollen tube guidance (de Nettancourt 2001, Goto et al 2011). However, the molecular basis of these mechanisms of pollination is still largely unclear (Hiroi et al 2013). …”
Section: Introductionmentioning
confidence: 99%